The Influence of Reading Interest in Buginese on the Learning Achievement of the Bugis Language of Class Xi Students of SMA Negeri 2 Barru - Hikmawati Hikmawati; Idawati Idawati (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
Abstract:The Influence of Reading Interest in Buginese on the Learning Achievement of the Bugis Language of Class Xi Students of SMA Negeri 2 Barru. This research is a quantitative research that aims to: (1) describe the interest in reading Bugis language of class XI students of SMA Negeri 2 Barru; (2) describe the learning achievement of Bugis language students of class XI SMA Negeri 2 Barru; (3) to prove whether or not there is an influence of interest in reading Bugis language on the achievement of learning Bugis language for class XI students of SMA Negeri 2 Barru. The population in this study were all students of Class XI SMA Negeri 2 Barru, totaling 162 students, while the sample consisted of 61 students as the sample. The results showed that, (1) students' interest in reading Bugis language was in the low category, the average score was 62.89; (2) Bugis language learning achievement of class XI students of SMA Negeri 2 Barru is in the high category, the average value is 83.66; (3) the influence of interest in Bugis reading on Bugis language learning achievement of class XI students of SMA Negeri 2 Barru proves that there is no significant influence between interest in reading Bugis language on students' Bugis language learning achievement, with data analysis showing tcount < ttable (1,229< 1.671) with an error level of 0.05 withthe number of N = 61.